Systematic Review and Meta-analysis for Surgery Versus Stereotactic Radiosurgery for Jugular Paragangliomas. Issue 3 (31st March 2023) - Campbell, James C.; Lee, Jessica W.; Ledbetter, Leila; Wick, Cameron C.; Riska, Kristal M.; Cunningham, Calhoun D.; Russomando, Alessandra C.; Truong, Tracy; Hong, Hwanhee; Kuchibhatla, Maragatha; Kaylie, David M.
Abstract : Objective: Comprehensively analyze tumor control and treatment complications for jugular paraganglioma patients undergoing surgery versus stereotactic radiosurgery (SRS). Databases Reviewed: EMBASE, Medline, and Scopus. Methods: The databases were searched for English and Spanish articles from January 1, 1995, to January, 1, 2019, for studies reporting tumor control and treatment side effects regarding patients with jugular paraganglioma treated with surgery or SRS. Main outcome measures included short-term and long-term tumor recurrence, as well as postintervention complications. Results: We identified 10, 952 original abstracts, 705 eligible studies, and 107 studies for final data extraction. There were 3, 498 patients—2, 215 surgical patients and 1, 283 SRS patients. Bayesian meta-analysis was applied to the extracted data, with tau measurements for study heterogeneity. SRS tumors were larger (3.9 cm 3 versus 8.1 cm 3 ). Meta-analysis results demonstrated low rates of long-term recurrence for both modalities (surgery, 15%; SRS, 7%), with SRS demonstrating lower rates of postintervention cerebrospinal fluid leak, dysphagia, and cranial nerve Vll, lX, X, Xl, or Xll palsies. Conclusions: This study demonstrates excellent control of jugular paragangiomas with both surgery and SRS, with higher rates of lower cranial neuropathies, dysphagia, and cerebrospinal fluid leaks among surgical patients.